2019
DOI: 10.1302/0301-620x.101b7.bjj-2018-1492.r1
|View full text |Cite
|
Sign up to set email alerts
|

Increased utilization of constraint in total knee arthroplasty following anterior cruciate ligament and multiligament knee reconstruction

Abstract: Aims Anterior cruciate ligament (ACL) and multiligament knee (MLK) injuries increase the risk of development of knee osteoarthritis and eventual need for total knee arthroplasty (TKA). There are limited data regarding implant use and outcomes in these patients. The aim of this study was to compare the use of constrained implants and outcomes among patients undergoing TKA with a history of prior knee ligament reconstruction (PKLR) versus a matched cohort of patients undergoing TKA with no history of PKLR. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
0
23
1
1
Order By: Relevance
“…30 The authors did not find any difference between groups in postoperative knee ROM, patient-reported outcomes, or incidence of revision surgery. 30…”
Section: Future Researchmentioning
confidence: 86%
See 2 more Smart Citations
“…30 The authors did not find any difference between groups in postoperative knee ROM, patient-reported outcomes, or incidence of revision surgery. 30…”
Section: Future Researchmentioning
confidence: 86%
“…James et al analyzed 188 patients with prior ACL reconstruction and 35 patients with prior multiligament reconstruction who underwent TKA, and found they had a significantly higher use of constrained implants at the time of TKA when compared with controls without prior ligament reconstruction. 30 The authors did not find any difference between groups in postoperative knee ROM, patientreported outcomes, or incidence of revision surgery. 30 Finally, further study is needed to determine if differences between old and new ACL fixation implants have effect on subsequent TKA.…”
Section: Future Researchmentioning
confidence: 88%
See 1 more Smart Citation
“…Although several authors have reported no increase in complications for ACL-TKA compared with primary TKA, others have noted increased complication rates 9-12,14 . Watters et al found that the risk of reoperation in patients undergoing ACL-TKA was 5.5 times higher than that for patients undergoing primary TKA 10 .…”
Section: Conversion Tka After Prior Ligament Reconstructionmentioning
confidence: 97%
“…The use of constrained implants increases with the complexity of prior ligament reconstruction. James et al compared 223 patients who had undergone previous ACL or multiligamentous knee reconstruction with a matched cohort of 223 patients who underwent primary TKA 14 . Constrained implants were used in 17.9% of patients who underwent primary TKA, 29.3% of patients who underwent ACL-TKA, and 60.0% of patients who underwent conversion TKA after multiligamentous reconstruction 14 .…”
Section: Conversion Tka After Prior Ligament Reconstructionmentioning
confidence: 99%